Application of a low-pressure arc discharge for formation of hard diffusion surface layers - Koval N. N. Nikolay Nikolaevich; Grigoriev S. V.; Ivanov Yu. F. Yuriy Fedorovich; Lopatin I. V.; Strumilova Т. V.; Shirinkina A. V. (2004, 2004)
Title screen